Key Success Factors in the Transfer of Web-Based Training A case study on commercial training at Volvo Cars done in collaboration with Semcon - Rosdahl, Ida; Bill, Jim (My University, 2016)
Training transfer is a well-studied research area. However, what factors that affect transfer from web-based training in corporate contexts need to be studied further. This case study sought to provide a better understanding on transfer of web-based training in the context of commercial training at Volvo Cars. An exploratory and mixed methodology approach was used, by combining a survey sent to sales consultants with interviews carried out with trainers working with sales consultant training. Six factors and their relation to training transfer were assessed in four national markets. From correlation analysis, learning, relatability to work life, learner control, training framing and expected outcomes were all found to positively correlate with transfer. These results imply, among other things; That learning is related to transfer; That web-based training needs to feel relevant and well-adapted to trainees’ work life; That extrinsic and intrinsic rewards are correlated with transfer performance. Statistically significant differences in transfer rating could also be observed between the four markets. This imply that how the training program is designed and what attitudes there are towards web-based training in the market influence the transfer outcome. The results of the study also provide suggestions on interesting topics for future research in the field of transfer of web-based training, for example how time pressure affect transfer performance, and how web-based training should be implemented in order to maximize transfer outcome.
Keywords: Annan data- och informationsvetenskap; Other Computer and Information Science